2019
DOI: 10.13171/mjc851907103ko
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of textile azo dye degradation by electrochemical oxidation using Box-Behnken Design

Abstract: Degradation of textile azo dye solutions containing Methyl Orange by anodic oxidation using an electrochemical reactor was studied. The combined effect of independent parameters (current intensity, initial pH and electrolysis time) on color removal efficiency was investigated and optimized using response surface methodology. A Box-Behnken design was successfully employed for experimental design. The obtained quadratic model was statistically tested using analysis of variance (ANOVA). Results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…According to these graphs, at low [NaCl], COD removal efficiency increases with current density. In other words, increasing current density leads to the generation of a large quantity of active chlorine species that rapidly react with organic pollutants, leading to greater degradation of the organic matter (6,41). Furthermore, higher current densities contribute to a reduction in the efficiency of the process generating low hypochlorite, which converts to a chloro-oxidant of higher oxidation states and is expressed as Eq.…”
Section: Influence Of the Electrolysis Parameter On Cod Removal Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…According to these graphs, at low [NaCl], COD removal efficiency increases with current density. In other words, increasing current density leads to the generation of a large quantity of active chlorine species that rapidly react with organic pollutants, leading to greater degradation of the organic matter (6,41). Furthermore, higher current densities contribute to a reduction in the efficiency of the process generating low hypochlorite, which converts to a chloro-oxidant of higher oxidation states and is expressed as Eq.…”
Section: Influence Of the Electrolysis Parameter On Cod Removal Efficiencymentioning
confidence: 99%
“…Various methods are currently employed for the removal of organic matter from textile wastewater. Although biological, chemical, and physical methods are used for treating dyes (i.e., biological oxidation, incineration, electrocoagulation, adsorption, ozonation, coagulation, and the like), they cannot sufficiently degrade these effluents (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…They have achieved 85% COD reduction using ruthenium oxide coated titanium anode. Oukili & Loukili (2019), performed the degradation of textile azo dye Methyl Orange a cylindrical platinized titanium (Ti/Pt) grid as anode. The author reported that 98.51% of color removal was achieved.…”
Section: Introductionmentioning
confidence: 99%